2009
DOI: 10.1093/nar/gkn1069
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression modulation is associated with gene amplification, supernumerary chromosomes and chromosome loss in antimony-resistant Leishmania infantum

Abstract: Antimonials remain the first line drug against the protozoan parasite Leishmania but their efficacy is threatened by resistance. We carried out a RNA expression profiling analysis comparing an antimony-sensitive and -resistant (Sb2000.1) strain of Leishmania infantum using whole-genome 70-mer oligonucleotide microarrays. Several genes were differentially expressed between the two strains, several of which were found to be physically linked in the genome. MRPA, an ATP-binding cassette (ABC) gene known to be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(219 citation statements)
references
References 68 publications
8
204
1
6
Order By: Relevance
“…A copy of the targeted gene was always present as a result of chromosome duplications (tri-or tetrasomy), wholegenome duplication, or translocation of the chromosome fragment carrying the target gene. Aneuploidy was also observed in laboratory strains of L. major and L. infantum after induction of drug resistance: transcriptional profiling using microarrays identified altered expression of genes on six different chromosomes in both species [10,11]. Quantitative Southern blot and comparative genomic hybridizations confirmed that the variation in expression corresponded to changes in the copy number of these chromosomes.…”
Section: The Flexible Genomes Of Leishmaniamentioning
confidence: 83%
See 2 more Smart Citations
“…A copy of the targeted gene was always present as a result of chromosome duplications (tri-or tetrasomy), wholegenome duplication, or translocation of the chromosome fragment carrying the target gene. Aneuploidy was also observed in laboratory strains of L. major and L. infantum after induction of drug resistance: transcriptional profiling using microarrays identified altered expression of genes on six different chromosomes in both species [10,11]. Quantitative Southern blot and comparative genomic hybridizations confirmed that the variation in expression corresponded to changes in the copy number of these chromosomes.…”
Section: The Flexible Genomes Of Leishmaniamentioning
confidence: 83%
“…By contrast, chromosome gain or loss (aneuploidy) in multicellular eukaryotes is either lethal or results in severe abnormalities, for example trisomy of chromosome 21 in humans with Down syndrome [6]. Despite the predominantly negative effects of aneuploidy, supernumerary chromosomes have been reported in tumor cells, yeast, and recently the protozoan Leishmania [7][8][9][10][11].…”
Section: The Flexible Genomes Of Leishmaniamentioning
confidence: 99%
See 1 more Smart Citation
“…3A). Reduced RNA levels in Leishmania are usually due to a decrease in gene copy number (61,62), although other mechanisms may also occur (63). Interestingly, in the yeast S. cerevisiae that also transports AdoMet, resistance to SNF was shown to correlate with loss of function mutations in the AdoMet transporter Sam3 (20).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mode of SbIII's action against Leishmania is poorly understood, mechanisms of resistance have been extensively described and involve the modulation of SbIII detoxifying pathways (36,37), altered uptake (19,38), increased efflux (39), and intracellular sequestration mediated by the ABC-thiol transporter multidrug resistance protein A (MRPA) (37,(40)(41)(42). The Cos-Seq screen for SbIII revealed 11 enriched cosmids ( Fig.…”
Section: High-throughput Screening Of the Five Major Antileishmanialmentioning
confidence: 99%